Gene Expression in Rainbow Trout (Oncorhynchus mykiss), Nile Tilapia (Oreochromis niloticus) and White Sturgeon (Acipenser transmontanus) Erythrocytes under Differing in vitro Glycemic Conditions - Powell, Madison; Kennedy, Tracy; Faler, Joyce; Hardy, Ronald (Avances en Nutrición Acuicola, 2013)
Rainbow trout (Oncorhynchus mykiss), Nile tilapia (Oreochromis niloticus) and white sturgeon (Acipenser transmontanus) blood cells were maintained in vitro over a 24 h period under different glycemic conditions to compare cellular response to prolonged hyperglycemia. In rainbow trout, facilitated glucose transporter 1 (GLUT 1) expression was upregulated within 1 h regardless of glucose concentration and returned to levels similar to initial quantitative values within 24 h. Likewise, expression of heat shock 70 protein (Hsp 70) was also significantly upregulated after 1 h and remained higher under hyperglycemic conditions compared to normoglycemia until 24 h. Expression of constitutive heat shock protein 90 (Hsp 90) showed significant individual variation but remained unchanged. Expression of GLUT 1 in Nile tilapia remained unchanged under normoglycemic conditions but steadily increased over time with hyperglycemia. Hsp70 and Hsp 90 expression in Nile tilapia was highly variable over time with significant increases observed within 1 h and expression of both genes remaining elevated after 24 h. Significant apoptosis was observed with white sturgeon blood cells under 5 mM and 20 mM glucose in vitro. Significantly lower glucose concentrations (0 mM and 2 mM) were required for sturgeon cells to survive. Facilitated glucose transport across membranes via GLUT 1 is responsive to extracellular glucose levels in a variety of fish species, suggesting GLUT 1 may be important in cellular functionality under hyperglycemic conditions.